The role of mobile money innovations in transforming unemployed women to self-employed women in sub-Saharan Africa - Simplice Asongu; Sara Le Roux (African Governance and Development Institute (AGDI), 2023)
The study examines how mobile money innovations transform unemployed women to self-employed women. The empirical evidence is based on interactive quantile regressions focusing on data in 44 countries from sub-Saharan Africa for the period 2004 to 2018. The hypothesis that mobile money innovations transform female unemployment to female self-employment is tested. Eight mobile money innovation dynamics presented in four categories are employed. Three main common findings are apparent from interactions between female unemployment, eight mobile money innovation dynamics and female self-employment: (i) the investigated hypothesis is valid exclusively at the top quantiles of female self-employment; (ii) the net effects are consistently negative and (iii) the corresponding conditional or interactive effects upon which the net effects are based are consistently positive. This is an indication that critical masses at which money innovation innovations have an overall positive net effect on female self-employment are apparent. The corresponding mobile money innovation policy thresholds at which the net effects on female self-employment change from negative to positive are provided. Policy implications are discussed.
Keywords: G20; O40; I10; I20; I32; 330; Mobile phones; financial inclusion; women; inequality; sub-Saharan Africa